2023
DOI: 10.1002/psp.2657
|View full text |Cite
|
Sign up to set email alerts
|

In and out of privileged and disadvantaged neighbourhoods in Sweden: On the importance of country of birth

Abstract: Moves into and out of privileged neighbourhoods as well as moves into and out of disadvantaged neighbourhoods in metropolitan Sweden are studied using register data on all moves by adults that took place between 2004 and 2006. Based on estimated multivariate models, we find that, for all four types of moves, age, education, household income, household composition and its changes, as well as labour market status and its changes, matter. However, in addition, where the person was born can matter, as, with some e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…There are several factors with potentially negative effects on the evolution of this indicator, and there are a number of pre-concerns as mentioned in the existing literature. Pre-factors such as unsustainable growth in the number of migrants [80][81][82], deteriorating living standards, rising house prices, and gentrification [83,84] are considered. Secondly, it can be observed that the Eastern European countries (Bulgaria, Romania, Poland, Slovenia) are registering a very rapid rate of decrease in the housing deprivation rate, which demonstrates once again, if it were needed, the massive depopulation of these countries, with potentially significant long-term negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors with potentially negative effects on the evolution of this indicator, and there are a number of pre-concerns as mentioned in the existing literature. Pre-factors such as unsustainable growth in the number of migrants [80][81][82], deteriorating living standards, rising house prices, and gentrification [83,84] are considered. Secondly, it can be observed that the Eastern European countries (Bulgaria, Romania, Poland, Slovenia) are registering a very rapid rate of decrease in the housing deprivation rate, which demonstrates once again, if it were needed, the massive depopulation of these countries, with potentially significant long-term negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Whether a person is native-born in a Nordic country is not a perfect indicator of their ability to integrate into Nordic society. However, country of birth has shown to be a robust indicator of integration potential (Gustafsson & Österberg 2022).…”
Section: Measuring Identitymentioning
confidence: 99%

State of the Nordic Region 2024

Norlén,
Heleniak,
Sánchez Gassen
et al. 2024
“…Several studies have demonstrated the widening gap in social inequalities in Sweden. They have highlighted not only the increasing socio-economic gap and its correlation to housing segregation but also how segregation is entangled with racial divisions within Swedish society (Molina 1997;Andersson and Molina 2018;Malmberg et al 2018;Bursell 2021;Gustafsson and Österberg 2023). Socio-economic and racial housing segregation also relate to the labour market segregation in which racial discrimination based on having immigrant background has been extensively studied (Bråmå 2007;Ahmed and Ekberg 2016;Tibajev 2016;Vernby and Dancygier 2018;Hammarstedt 2020).…”
Section: Introductionmentioning
confidence: 99%